The novel TFEB agonist desloratadine ameliorates hepatic steatosis by activating the autophagy-lysosome pathway - Lin, Jieru; Huang, Chunhuan; Zhao, Jingye; Li, Lu; Wu, Zhenwei; Zhang, Tingyu; Li, Yuyin; Li, Wei; Guo, Baoqiang; Liu, Zhenxing; Diao, Aipo (Frontiers in Pharmacology, 2024)
The autophagy-lysosome pathway plays an essential role in promoting lipid catabolism and preventing hepatic steatosis in non-alcoholic fatty liver disease (NAFLD). Transcription factor EB (TFEB) enhances the autophagy-lysosome pathway by regulating the expression of genes related to autophagy and lysosome biogenesis. Therefore, targeting TFEB provides a novel strategy for the treatment of lipid metabolic diseases. In this study, the antiallergic drug desloratadine was screened and identified as a novel TFEB agonist. Desloratadine effectively induced translocation of TFEB to the nucleus and promoted autophagy and lysosome biogenesis. Desloratadine-induced TFEB activation was dependent on AMPK rather than mTORC1. Moreover, desloratadine treatment enhanced clearance of lipid droplets in cells induced by fatty acids oleate and palmitate. Furthermore, high-fat diet (HFD) induced obesity mouse model experiments indicated treatment with desloratadine markedly reduced the body weight of HFD-fed mice, as well as the levels of hepatic triglycerides and total cholesterol, serum glutamic pyruvic transaminase and glutamic-oxaloacetic transaminase. Oil red O staining showed the liver fat was significantly reduced after desloratadine treatment, and H&E staining analysis demonstrated hepatocellular ballooning was improved. In addition, autophagy and lysosomal biogenesis was stimulated in the liver of desloratadine treated mice. Altogether, these findings demonstrate desloratadine ameliorates hepatic steatosis through activating the TFEB-mediated autophagy-lysosome pathway, thus desloratadine has an exciting potential to be used to treat fatty liver disease.